Conhecimento de si e liberdade interna : uma exploração filosófica da interioridade nos estoicos e em Santo Agostinho - Musella, Pedro Brosina Alencastro (2023)
This dissertation proposes a philosophical study on the notions of self knowledge and inner freedom in the thought of Saint Augustine and in the philosophical school of Stoicism. Such an endeavor will be carried out based on an analysis of the conceptual basis present in both cases, with the aim of highlighting similarities between them and demonstrating how the work of the Stoics represents an influence in Augustine's thought and how he, in turn, expanded the work initiated by these thinkers. Given the focus of this project, it will deal with authors whose field of action remains, to a large extent, the human mind, and the proposed analysis will be carried out in such a way as to take into account not only a philosophical but also a psychological interpretation of the topics worked on, through comparisons with authors from the field of psychology, with the aim of elucidating how the work of Augustine and the stoics is found directly or indirectly also in this area of study. The proposed hypothesis is that Augustine, while working with concepts originally attributed to Stoic thinkers, was responsible for a great enrichment of the philosophical understanding and expansion of the Stoic theses about the mind, becoming in this way a pioneer in the study of concepts that would later turn out to inspire questions elaborated by psychology authors who indirectly continued the work of Augustine and who today provide a new lens through which to interpret his work as a source for the knowledge and study of the Self as well as of internal freedom.